Waterborne coating compositions based on self-crosslinking polyurethane dispersions

By esterifying the epoxy silane of anionic polyurethane particles and crosslinking the transition metal compound particles in the aqueous polyurethane dispersion, the health hazards of solvent coatings and the low water resistance of the aqueous dispersion are solved, and non-toxic and solvent-free, Non-flammable high-performance polyurethane coating.

CN114514258BActive Publication Date: 2025-01-14SAINT-GOBAIN WEBER SA
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202080072177.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-10-17
Filing Date
2020-10-13
Publication Date
2025-01-14
Estimated Expiration
2040-10-13

AI Technical Summary

Technical Problem

Solvent-based polyurethane coatings have health hazards and low water resistance problems in waterproof building materials, and the use of water-based polyurethane dispersions in humid environments is unsatisfactory, with long drying time, high water absorption and deteriorating mechanical properties.

Method used

The anionic charge density and the durability of the coating are adjusted by reacting the carboxylate pendant of the anionic polyurethane particles with epoxy silane for esterification, and using water-insoluble transition metal compound particles as crosslinking agents.

Benefits of technology

A non-toxic, self-crosslinked aqueous polyurethane dispersion was prepared, with good drying properties, water resistance and mechanical properties, equivalent to a solvent-based polyisocyanate/polyol system, suitable for waterproof coatings and adhesives.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to an aqueous polyurethane dispersion, which comprises: anionic polyurethane particles, which contain a formula of -COO ‑ M + The free carboxylate side groups and the carboxylate side groups of + Crosslinked particles made of water-insoluble transition metal compounds are prepared to neutralize the cations generated by carboxylic acid groups with a base, the pendant carboxylate groups being generated by esterification of free carboxylic acid groups with epoxysilanes. It also relates to a method for coating a substrate, comprising applying such an aqueous polyurethane dispersion to a substrate and drying it, preferably without applying any heat or radiation.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to aqueous self-crosslinking compositions based on film-forming polyurethane dispersions which are functionalized with anionic carboxylate groups partially esterified with epoxysilanes and which also contain transition metal compound particles as crosslinkers.

[0002] Solvent-based polyurethane coatings have been used for several years in the field of waterproof building materials technology, such as in roof and balcony systems. These solvent-based waterproofing compositions are well known for their durability and ease of application. They provide a qualified durability of 25 years (ETAG 005, Guidelines for European Technical Approval of Liquid Applied Roof Waterproofing Kits).

[0003] However, solvent-based compositions present a health risk to the user due to the flammability of the solvent and the presence of free isocyanate monomers when present in concentrations > 0.1%, which are considered to be harmful in contact with the skin and in case of inhalation.

[0004] For the reasons stated above, solvent-based polyurethane coatings are currently limited primarily to professional use.

[0005] In all kinds of technical fields there is a general trend towards converting solvent-based systems to aqueous systems.

[0006] Thus, film-forming aqueous polyurethane dispersions (PUDs) have been proposed for several years. They are free of isocyanate monomers and contain no residual isocyanate groups on the polymer.

[0007] However, their use in the field of gluing or coating of substrates intended for use in humid environments, especially in the field of waterproofing, is unsatisfactory because they have very long drying times, late rain resistance, and suffer from high water absorption and subsequent decay of their mechanical properties even weeks after application, film formation and water evaporation. The low water resistance is attributed to the high charge density of PUDs (charges stabilizing the surfactant or polymer chains) and the fact that film formation is due only to the coalescence of polymer particles without accompanying chemical crosslinking.

[0008] In order to overcome the low water resistance of PU films, crosslinkable silyl-terminated PUDs have been proposed (see, for example, US 6,046,295, US 5,919860 and US 2017 / 0174815). In these documents, isocyanate-terminated prepolymers are reacted with silane compounds containing two or three alkoxysilyl groups and isocyanate-reactive groups such as -NH, OH or SH. However, such silyl-terminated PUDs still do not always allow the preparation of fast-drying and fully water-resistant coatings or adhesives. In fact, since the crosslinking silyl groups are only present at the ends of the polymer chains, their density cannot be increased at will.

[0009] The present invention is based on the idea of ​​introducing crosslinking silyl groups not as terminal groups but as pendant groups all along the polyurethane chain, thereby freely adjusting the number of silyl groups, ie the number of crosslinking groups.

[0010] Thus, the inventors have an anionic polyurethane functionalized by reacting a portion of the pendant carboxylate groups with epoxy silanes. The epoxy groups of the silane esterify with the carboxylate groups of the anionic polyurethane, thereby reducing the overall anionic charge density of the dispersed polymer particles and covalently bonding the alkoxysilyl groups to the polymer. The reduction in anionic charge on the PU particles can be easily followed by monitoring the reduction in negative zeta potential during the reaction time.

[0011] During their experimental studies, the inventors have observed that it is difficult and undesirable to esterify more than about half of the PUD carboxylate groups. The remaining unreacted carboxylate groups provide stability to the silyl-functional PU dispersion. However, if too much anionic charge is left on the PUD after esterification, their hydrophilicity does not allow sufficient reduction of water absorption and improvement of the durability and mechanical properties of the resulting dried coating.

[0012] The inventors have surprisingly found, however, that by using specific crosslinked particles as additional crosslinking agents, it is possible to utilize these residual anionic charges and thereby further improve the durability of the final coating without destabilizing the polyurethane dispersion prior to application to the substrate.

[0013] The first subject of the present application is an aqueous polyurethane dispersion comprising:

[0014] - anionic polyurethane particles comprising the formula -COO - M + The free carboxylate side groups and the carboxylate side groups of + to neutralize with a base the cations generated by the carboxylic acid groups, the pendant carboxylate groups being generated by esterification of the free carboxylic acid groups with epoxysilanes,

[0015] - Crosslinked particles made of water-insoluble transition metal compounds.

[0016] In a second aspect, the present invention relates to a method for preparing such an aqueous polyurethane dispersion, said method comprising

[0017] - esterification of the anionic polyurethane dispersion by reacting the pendant carboxylate groups with epoxy silanes,

[0018] - Dispersing water-insoluble transition metal compound particles in anionic polyurethane dispersion.

[0019] The polyurethane dispersions used in accordance with the invention are known in the prior art and their preparation is described, for example, in US Pat. No. 7,345,110.

[0020] Isocyanate-terminated prepolymers are first prepared by reacting a polyol with a stoichiometric excess of a polyisocyanate, the NCO / OH ratio generally being comprised between 1.2 and 5.

[0021] The polyisocyanate may be an aliphatic polyisocyanate, such as, for example, 1,6-hexamethylene diisocyanate, isophorone diisocyanate, 2,4-hexahydrotoluene diisocyanate, 2,6-hexahydrotoluene diisocyanate, dicyclohexylmethane diisocyanate, tetramethylxylene diisocyanate, norbornane diisocyanate, bis-isocyanatomethyl)cyclohexane, tetramethylene-1,4-diisocyanate, cyclohexane-1,4-diisocyanate, 1,12-dodecane diisocyanate and 2,2,4-trimethylhexamethylene diisocyanate.

[0022] Aromatic polyisocyanates can also be used. They are selected, for example, from xylylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate and methylene diphenyl diisocyanate.

[0023] The polyols are, for example, polyether polyols, polyester polyols or polycarbonate polyols, or mixtures thereof.

[0024] To introduce anionic charges into the polymer, dihydroxylated carboxylic acids such as dimethylol propionic acid (DMPA) are copolymerized together with polyols and polyisocyanates.

[0025] The resulting isocyanate prepolymer with pendant carboxylic acid groups is then dispersed in water under shear and an amine-type base is added to neutralize the carboxylic acid groups.

[0026] The third step in the preparation of anionic PUDs is chain extension by the addition of polyamines, usually diamines, which react with isocyanate groups to form urea bonds. An isocyanate-free poly(urea / urethane) with neutralized pendant carboxylate groups is thus obtained.

[0027] Preferred PUDs are prepared from aromatic diisocyanates and polyether-polyols.

[0028] As described above, the anionic carboxylate groups are partially esterified by reaction with the epoxysilane, and the remaining unesterified carboxylate groups are available to stabilize the PUD and to crosslink with the transition metal compound particles when the coating is dried.

[0029] The inventors have found that PUD should preferably not have too high anionic carboxylate groups before reacting with epoxysilane. Their acid value (the mass of KOH required to neutralize one gram of chemical in milligrams) preferably includes 5 to 25, more preferably 10 to 18, and even more preferably 12 to 17.

[0030] PUDs with acid values ​​above the upper limit of the above range require too high amounts of epoxy silane and / or crosslinked particles. Adding too much epoxy silane during the esterification step of the carboxylate side groups will lead to early gelation / coagulation of the dispersion and will not be able to prepare a stable self-crosslinked PU dispersion. On the other hand, adding very high levels of crosslinked particles means using large amounts of dispersant (surfactant), which will make the resulting dried coating more hydrophilic and less water resistant.

[0031] Controlling the total initial anionic charge of the non-esterified PUD, selecting two different types of crosslinkers (epoxy silane & crosslinking particles) and using each of them in appropriate amounts, enabled the inventors to prepare water-based, non-toxic, self-crosslinking polyurethane dispersions that have a shelf life of at least several months and, after drying and crosslinking, produce polyurethane coatings with water resistance and mechanical properties comparable to those obtained from solvent-based polyisocyanate / polyol systems.

[0032] Any water-soluble epoxysilane can be used to partially esterify the anionic carboxylate groups of the PUD. Monomeric epoxysilanes contain a single epoxy group, also known as a glycidyl group, and two or three hydrolyzable alkoxy groups attached to silicon. Preferred monomeric epoxysilanes are selected from 3-glycidyloxypropyl-trialkoxysilanes, 3-glycidyloxypropyl-dialkoxyalkylsilanes, epoxycyclohexylethyltrialkoxy-silanes, epoxycyclohexyl-ethyldialkoxyalkylsilanes. The alkoxy group is preferably an ethoxy group.

[0033] The inventors have also used water-soluble epoxysilane oligomers comprising short siloxane chains with pendant epoxy groups. The preparation of such oligomers is described, for example, in EP1896522 and they are available from Momentive under the reference CoatOSil MP 200.

[0034] The epoxy silane is added to the PUD in an amount comprising 0.3 to 5.0 wt %, preferably 0.4 to 4.0 wt %, and more preferably 0.5 to 3.0 wt % relative to the dry weight of the PUD. When the amount of epoxy silane added to the PUD is higher than about 4.0 to 5.0 wt %, the reaction mixture gels during the reaction time and is no longer suitable as a coating composition. For amounts lower than about 0.3 to 0.4 wt %, the remaining anionic charge density on the PUD is too high and an excess of crosslinked particles needs to be added. However, the amount of crosslinked particles cannot be increased at will because there is a risk of sedimentation or an excessive amount of dispersant is required.

[0035] To react PUD with epoxysilane, epoxysilane is slowly, preferably dropwise, added to PUD at room temperature and under stirring, and the mixture is allowed to react for at least several hours. It is not necessary to keep the reaction mixture under stirring, nor to heat the reaction mixture. The reaction time at room temperature (20° C.) generally includes 10 hours to 100 hours, more preferably 20 to 80 hours, more preferably 40 to 75 hours.

[0036] The crosslinked particles are preferably incorporated into the polyurethane dispersion after a portion of the anionic carboxylate groups have been esterified with the epoxysilane.

[0037] The transition metal compounds forming the crosslinked particles used in the present invention must be insoluble in the aqueous phase of the PUD, water-insoluble transition metal compounds being defined in this application as compounds having a solubility of less than 0.001% in distilled water at 20°C. In fact, the PUD composition must not contain significant amounts of free multivalent transition metal cations, which would immediately lead to premature crosslinking of the carboxylated polymer and then cause gelation, precipitation or sedimentation of the dispersion. Thus, the PUD compositions of the present invention are substantially free of free multivalent transition metal ions, i.e. they contain less than 0.1% by weight, preferably less than 0.01% by weight, of water-soluble transition metal salts, such as potassium zirconium carbonate or ammonium zirconium carbonate as described, for example, in US 4,061,720.

[0038] The transition metal compound is preferably selected from transition metal salts, transition metal oxides and transition metal hydroxides. Particularly preferred are transition metal oxides. The transition metal is advantageously selected from zinc, aluminum, tin, tungsten and zirconium, preferably consisting of zinc, aluminum, tin and tungsten, with zinc and aluminum being particularly preferred. The inventors have obtained excellent results with zinc oxide particles.

[0039] Crosslinking carboxylated polymers by transition metal compound particles is known and is described, for example, in US 8,236,903 and US 2008 / 0255273. These prior art documents describe in particular nanoparticles, i.e. particles with a submicron particle size, which, when fully incorporated into a polymer matrix, provide a large contact surface for effective crosslinking. The inventors were surprised when they found that non-nanoscale particles can also be used to effectively contribute to the crosslinking of carboxylated polyurethane dispersions. Compared to the nanoparticles described in the literature, these particles, which have an average particle size greater than about 1 micron, are much cheaper and less problematic from an environmental point of view.

[0040] For the reasons described above, the water-insoluble crosslinked particles made of a transition metal compound used in the present invention preferably have a weight average particle diameter measured by laser diffraction of 1.0 μm to 20 μm, preferably 1.5 μm to 10 μm, inclusive.

[0041] The amount of the crosslinked particles used in the present invention is such that the weight ratio of the crosslinked particles to the anionic polyurethane particles is preferably comprised between 0.01 and 0.40, more preferably between 0.2 and 0.25, and particularly between 0.03 and 0.15.

[0042] It is necessary to effectively disperse the crosslinked particles and stabilize the dispersion so that the particles will not settle during storage. This can be achieved by incorporating sufficient amounts of dispersants and / or thickeners into the waterborne PUD along with the crosslinked particles.

[0043] Dispersants can be, for example, surfactants, preferably nonionic surfactants, and thickeners are typically water-soluble organic polymers such as cellulose derivatives, salts of polyacrylic acid and copolymers thereof, xanthan gum and polyvinyl alcohol, nonionic polyurethane associative thickeners. These adjuvants that help to disperse and stabilize transition metal compound particles should be used in fairly low amounts. Their hydrophilic nature can indeed impart durability to dry coatings or adhesives by promoting water absorption.

[0044] The total amount of dispersants and / or thickeners should not be higher than about 10% by weight relative to the dry weight of the PUD. It preferably comprises 1 to 10% by weight, more preferably 2 to 9% by weight, and especially 3 to 8% by weight relative to the dry weight of the PUD.

[0045] The polyurethane dispersion of the invention may also contain one or more mineral fillers in a total amount of 0.1 to 70% by weight, preferably 1.0 to 40% by weight, more preferably 5 to 30% by weight, relative to the total dry weight of the dispersion.

[0046] Of course, fillers are different from the transition metal compounds of the crosslinked particles. They can be selected, for example, from calcium carbonate, barium sulfate, clay, talc, dolomite, mica, silica sand, crushed basalt, kaolin, in particular calcined kaolin.

[0047] The PUD comprising anionic polyurethane with partially esterified carboxylate groups and crosslinked particles can also be mixed with any other type of polymer latex. Such latex can be selected from, for example, poly(vinyl acetate / ethylene) latex, poly(acrylate) latex, poly(styrene / acrylate) latex, poly(vinyl acetate) latex, poly(styrene / butadiene) latex, poly(acrylate / vinyl acetate) latex, poly(vinyl acetate / versatate) latex, poly(vinyl propionate / acrylate) latex, natural rubber latex, pre-vulcanized natural rubber latex, poly(styrene-butadiene / styrene) latex or poly(vinyl acetate / ethylene / vinyl chloride) latex, or a mixture thereof. The latex mixed with the PUD preferably also comprises anionic groups that can be crosslinked with the crosslinked particles used in the present invention.

[0048] It is also possible to combine the PUD of the present invention with an aqueous dispersion of any kind of bitumen.

[0049] When the above latex or asphalt dispersion is mixed with the above PUD, the respective amounts of PUD and latex / asphalt dispersion are such that the resulting dry coating or dry adhesive has acceptable durability and water resistance.

[0050] In preferred embodiments of the resulting PUD / latex blend or the resulting PUD / asphalt blend, the dry weight of the carboxylated and esterified polyurethane polymer should be higher than that of the latex or asphalt.

[0051] The water content of the polyurethane dispersion of the invention comprises 30% to 95%, preferably 35 to 75%, relative to the total weight of the dispersion. When the PUD is mixed with other latex or bitumen dispersions, the water content is understood to be the water content of the mixture of these dispersions.

[0052] The aqueous polyurethane dispersions of the present invention are self-crosslinking compositions, also known as one-component compositions, i.e., they do not require the introduction of a catalyst or any additional crosslinking agent prior to applying the dispersion to a substrate to be coated, treated, glued or bonded. This makes their use as coating compositions, primers, adhesives, binders, sealants, etc. very simple and convenient. The PUD of the present invention can be applied to a substrate or between two substrates and will dry without the application of energy in the form of heat or radiation. In the case where the PUD is applied between two substrates, at least one of them should be sufficiently porous or water permeable to allow water evaporation of the PUD.

[0053] Therefore, another subject of the present invention is a process for coating substrates, in particular for waterproofing substrates, comprising applying the above-described aqueous polyurethane dispersion to or between the substrates and allowing it to dry, preferably without applying any heat or radiation.

[0054] The self-crosslinking polyurethane dispersions of the present invention may also be used in combination with a second crosslinking component, such as, for example, a polyisocyanate component. Such a component should be easily mixed with the aqueous dispersion of the present invention. Water-dispersible polyisocyanates that can be used in combination with the PUD of the present invention are available, for example, as Bayhydur® from Covestro. When dispersed in the aqueous PUD of the present invention, these compounds are self-crosslinking and can enhance the resulting polymer coating.

[0055] The aqueous self-crosslinking polyurethane dispersion of the present invention can be used in various technical fields where it is necessary to form a water-resistant and temperature-resistant coating on a substrate or between substrates.

[0056] The PUD can be used, for example, as a coating composition, in particular a waterproofing composition for substrates, for example for exterior building substrates such as roofs, facades or balconies, as a coating composition for wood, flooring, stone, concrete, render, plaster, metal or polymer substrates, as an adhesive, as a sealant, as a primer.

[0057] PUDs can also be used to coat substrates to improve their durability, mechanical and / or chemical resistance.

[0058] They can also be used as primers for waterproofing substrates beneath tiles or as coatings for building elements such as roofs, industrial or decorative floors, basements, balconies, terraces, bridge elements. Example

[0059] Four aqueous polyurethane dispersions having the compositions listed in Table 1 below were prepared as follows:

[0060] Example 1: Preparation of an aqueous dispersion of anionic polyurethane, which was prepared from polyether-polyol, aromatic diisocyanate, dimethylol propionic acid and ethylenediamine as chain extender. The resulting polyurethane dispersion (PUD) had a dry matter content of 42% and an acid number of 16.1 mg KOH / g. 0.5% by weight (relative to the dry weight of PUD) of 3-glycidyloxypropyl-triethoxysilane was added dropwise to the PUD over a period of one hour. The container was closed and the mixture was allowed to react for 72 hours without stirring. After 72 hours of reaction, dispersant and defoamer were added with stirring. After stirring for 5 minutes, ZnO and fillers (barium sulfate, calcium carbonate) were immediately added and dispersed by high-speed mixing during 30 minutes. Finally, the viscosity was adjusted with a mixture of the remaining water, propylene glycol and thickener (non-ionic polyurethane associative thickener).

[0061] The particle size parameters of ZnO particles are as follows:

[0062] D 90 :9.83 µm; D 50 :3.35 µm,D10 :0.72 µm and D 平均 : 4.64 µm.

[0063] Comparative Example 2 was prepared as in Example 1, except that the PUD was not reacted with 3-glycidyloxypropyl-triethoxysilane and no ZnO particles were incorporated into the dispersion.

[0064] Comparative Example 3 was prepared as in Example 1, with the only difference being that the PUD was not reacted with 3-glycidyloxypropyl-triethoxysilane.

[0065] A comparative example was prepared as in Example 1, with the only difference being that no ZnO particles were incorporated into the composition.

[0066] Table 1

[0067] Example 1 (the present invention) Comparative Example 2 Comparative Example 3 Comparative Example 4 PUD 60 60 Epoxy Silane-PUD 60 60 ZnO 3 3 Dispersants 0.1 0.1 0.1 0.1 Defoaming agent 0.5 0.5 0.5 0.5 Barium sulfate 10 10 10 10 Barium carbonate 15 18 15 18 talc 5 5 5 5 Monopropylene glycol 1 1 1 1 Thickener 2 2 2 2 water 3.4 3.4 3.4 3.4

[0068] The polyurethane dispersion was then coated onto a polyethylene film at a wet thickness of 1 mm and allowed to dry / cure at room temperature for 7 or 28 days. The coating was then peeled off from the polyethylene substrate and the film was cut into samples. The film dried for 7 days was then weighed, immersed in distilled water at room temperature for 24 hours or 14 days, weighed again, and the weight gain (water absorption) was calculated and expressed relative to the initial dry weight of the sample. Mechanical properties, i.e. elongation at break (EaB) and tensile strength (TS) were measured before and after water immersion according to ASTM D412.

[0069] The results are shown in Table 2.

[0070] Table 2

[0071] Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 EaB after 7 days of curing 372 % 340 % 350 % 360 % EaB after 28 days of curing 305 % 285 % 320 % 335 % TS after 7 days of curing 5.40 MPa 3.20 MPa 3.70 MPa 3.90 MPa TS after 28 days of curing 5.45 MPa 3.95 MPa 4.10 MPa 4.30 MPa Water absorption after 24 hours of immersion 0.5 % 7.61 % 7.25 % 6.43 % Water absorption after 14 days of immersion 2.0 % 18.0 % 12.0 % 9.0 % EaB after 48 hours of immersion 410 % 810 % 620 % 600 % TS after 48 hours of immersion 4.91 MPa 2.70 MPa 3.40 MPa 4.05 MPa EaB after 14 days of immersion 546 % 950 % 750 % 710 % TS after 14 days of immersion 4.52 MPa 2.40 Mpa 3.20 Mpa 3.90 MPa

[0072] It can be seen that the polyurethane film of Example 1 cured much faster than the polyurethane films of Comparative Examples 2 to 4. Its tensile strength hardly increased after only 7 days of curing.

[0073] The film of Example 1 further absorbed much less water. Its water absorption after 24 hours of immersion was almost the same as that of a one-component solvent-based polyurethane resin (Mariseal® 250 from Maris Polymers) tested under the same conditions.

[0074] Most importantly, the degradation of the mechanical properties of the polyurethane film of the present invention (Example 1) during immersion was much less than that of the films of Comparative Examples 2-4.

[0075] Thus, these experimental examples show that the combined use of crosslinked particles of epoxy silane and transition metal compound particles produces a non-toxic, solvent-free, non-flammable, stable film-forming polyurethane dispersion which, when applied to a substrate, forms a water-resistant coating that exhibits good retention of its mechanical properties.

Claims

1. An aqueous polyurethane dispersion comprising: - anionic polyurethane particles comprising the formula -COO - M + The free carboxylate side groups and the carboxylate side groups of + to neutralize with a base the cations generated by the carboxylic acid groups, the pendant carboxylate groups being generated by esterification of the free carboxylic acid groups with epoxysilanes, - cross-linked particles made of water-insoluble zinc oxide, and - less than 0.01% by weight of a water-soluble transition metal salt, The anionic carboxylate groups are partially esterified by reaction with epoxysilane, and the remaining unesterified carboxylate groups can be used for crosslinking with zinc oxide particles. wherein the acid value of the aqueous polyurethane dispersion before reacting with the epoxy silane comprises 5 to 25, wherein the acid value is the mass of KOH required to neutralize one gram of chemical, in milligrams, and The epoxy silane is added to the aqueous polyurethane dispersion in an amount of 0.3 to 5.0 wt % relative to the dry weight of the aqueous polyurethane dispersion.

2. The aqueous polyurethane dispersion according to claim 1, wherein the weight ratio of the crosslinked particles to the anionic polyurethane particles is from 0.01 to 0.

40.

3. The aqueous polyurethane dispersion according to claim 1, wherein the weight ratio of the crosslinked particles to the anionic polyurethane particles is 0.2 to 0.

25.

4. The aqueous polyurethane dispersion according to claim 1, wherein the weight ratio of the crosslinked particles to the anionic polyurethane particles is 0.03 to 0.

15. 5 . The aqueous polyurethane dispersion of claim 1 , wherein the crosslinked particles have a weight average particle size of 1.0 μm to 20 μm as measured by laser diffraction. 6 . The aqueous polyurethane dispersion of claim 1 , wherein the crosslinked particles have a weight average particle size of 1.5 μm to 10 μm as measured by laser diffraction.

7. The aqueous polyurethane dispersion according to claim 1, wherein the epoxy silane is selected from 3-glycidyloxypropyl-trialkoxysilane, 3-glycidyloxypropyl-dialkoxyalkylsilane, epoxycyclohexylethyltrialkoxy-silane, epoxycyclohexyl-ethyldialkoxyalkylsilane and water-soluble epoxy silane oligomers.

8. The aqueous polyurethane dispersion according to claim 1, further comprising 0.1 to 70 wt% of a mineral filler.

9. The aqueous polyurethane dispersion according to claim 1, further comprising 1.0 to 40 wt% of a mineral filler.

10. The aqueous polyurethane dispersion according to claim 1, further comprising a dispersant and / or a thickener.

11. The aqueous polyurethane dispersion according to claim 10, wherein the dispersant is selected from nonionic surfactants.

12. The aqueous polyurethane dispersion according to claim 10, wherein the dispersant is selected from water-soluble organic polymers.

13. The aqueous polyurethane dispersion according to claim 1, wherein the amount of water is 30% to 95% relative to the total weight of the dispersion.

14. The aqueous polyurethane dispersion according to claim 1, wherein the amount of water is 35% to 75% relative to the total weight of the dispersion.

15. A method for preparing an aqueous polyurethane dispersion according to any one of claims 1 to 14, comprising - esterification of the anionic polyurethane dispersion by reacting the pendant carboxylate groups with epoxy silanes, - Dispersing water-insoluble zinc oxide particles in anionic polyurethane dispersion.

16. The method for preparing an aqueous polyurethane dispersion according to claim 15, wherein the amount of epoxy silane used for esterification is 0.4 to 4.0 wt% relative to the dry weight of the PUD.

17. The method for preparing an aqueous polyurethane dispersion according to claim 15, wherein the amount of epoxy silane used for esterification is 0.5 to 3.0 wt% relative to the dry weight of the PUD.

18. A method for coating a substrate, comprising applying an aqueous polyurethane dispersion according to any one of claims 1 to 14 to a substrate and allowing it to dry.

19. A method of coating a substrate, comprising applying an aqueous polyurethane dispersion according to any one of claims 1 to 14 to the substrate and allowing it to dry, without applying any heat or radiation.

20. Use of an aqueous polyurethane dispersion according to any one of claims 1 to 14 as waterproofing composition for substrates, as coating composition for wood, flooring, stone, concrete, plaster, stucco, metal or polymeric substrates, as adhesive, as sealant, as primer.

Citation Information

Patent Citations

  • Epoxy silane oligomer and coating composition containing same

    EP1896522A1

  • Particulate Filled Polymers

    US20080255273A1

  • Polyurethane-polyurea dispersions comprising hydrazine or hydrazide chain extenders

    US20170174815A1

  • Preparation of ammonium and potassium zirconium carbonates

    US4061720A

  • Aqueous polyurethane / urea dispersions containing alkoxysilane groups

    US5919860A